A Novel Technique to Restore a Large Maxillary Defect- A Case Report (Journal of Pharmaceutical Negative Results, 2022)
The causes of maxillary defects can be congenital or acquired in nature and management of these defects often require surgical removal of a part or almost the whole of the maxilla. This may result in establishment of oro-antral communication which ultimately hampers the daily routine activities of the patients such as speaking, swallowing, sneezing and coughing. Improvement of the defects with obturator prosthesis has been found to be beneficial to the patients. However, one of the main obstacles in restoring a large defect is the heaviness of the prosthesis which makes it non-retentive. To conquer these difficulties, diverse techniques are used to build up hollow bulb obturators. Here we report a case of large maxillary defect in a 75 year old male with Class I Aramany’s defect which was restored by a provisional obturator designed in the shape of a close hollow bulb using a clear and streamlined method for fabrication.